ENCAPSULATION OF BIOACTIVE COMPOUNDS BY COMPLEX COACERVATION - Silva, Thaiane Marques da (2015)
The bioactive compounds are chemicals found in plants and are widely known for bringing health benefits, so it can be designated as functional foods. However, they are sensitive to various factors found in the environment that are exposed primarily to tratogastrointestinal and, moreover, are lipophilic, therefore, have low solubility in aqueous media. In this sense, the encapsulation of these compounds is an alternative protection, and the provision of such compounds in suitable amounts. The complex coacervation microencapsulation is a technique commonly used for such compounds, besides having front advantages to other techniques such as the use of biopolymers, no use of toxic agents, among others. Currently, there are a lot of research in this direction, which will be presented in this paper. Thus, the present review aims to present the main bioactive compounds studied and encapsulated as well as the parameters for complex coacervation technique.